Faktor-faktor yang Mempengaruhi Efektivitas Pengelolaan Dana BOS Pada SMA dan Sederajat di Kecamatan Simo - Rosa Agestina; Yuwita Ariessa Pravasanti; LMS Kristiyanti (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2023)
This study aims to determine the influence between accountability, transparency, and parental participation and the effectiveness of management of BOS funds in empirical studies at SMA/SMK/MA/equivalent in Simo District, Boyolali Regency. This type of quantitative research uses primary data by distributing questionnaires to respondents. The population in this study were SMA/SMK/MA/equivalent schools in Simo District and parents of students related to the management of BOS funds. The sample selection method was random sampling so that 120 respondents were obtained consisting of school principals, vice principals, BOS treasurers, BOS operators, teachers, and students' parents. Based on the results of the t-test that has been carried out, it can be seen that accountability partially has no effect on the effectiveness of BOS fund management, transparency has a positive effect on the effectiveness of BOS fund management, and participation has a negative effect on the effectiveness of BOS fund management. However, based on the F test it is known that accountability, transparency, and parental participation simultaneously influence the effectiveness of BOS fund management